Efektivitas E-ABK: Analisis Beban Kerja di Dinas Pendidikan Kota Surabaya - Emirul Ibnu Nizar; Kalvin Edo Wahyudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research examines the effectiveness of E-ABK (Workload Analysis) in the Surabaya City Education Office. The aim of this research is: To find out how effective E-ABK is in the Surabaya City Education Office. The research method in this study uses a qualitative approach with descriptive research. This research wants to discuss the effectiveness of E-ABK (Workload Analysis) in the Surabaya City Education Office which consists of 5 indicators, namely Efficiency, Adequacy, Evenness, Responsiveness and Accuracy. This research uses primary data collection techniques in the form of observation, documentation and interviews, while secondary data uses the results of previous research with different loci. The research results show that the use of E-ABK (Workload Analysis) is in accordance with 5 indicators, namely Efficiency: Based on the data sources obtained, it is very supportive in assisting the process of filling in crew members. ASN employee resources that support the implementation of E-ABK can be said to be efficient if all ASN are able to understand the filling flow and complete it on time. ; Adequacy: The organization of regional apparatus in the Education Service has been carried out in accordance with the applicable mechanism, namely an analysis of workload on the organizational structure. The policy for structuring regional apparatus organizations in the Education Department has met the adequacy criteria. This can be seen from the fact that the organizational structuring policies implemented have met the needs of the city government organization itself. ; Alignment: By equalizing the workload, you can create a fairer and more equitable work environment where all employees can give their best. ; Responsiveness: Increasing responsiveness can increase efficiency, reduce waiting time, increase customer satisfaction, and increase employee morale. ; and Accuracy: The accuracy of the number of employees needed in the Surabaya City Education Department can be seen through the existing number which will later be determined and matched between the existing E-ABK and the existing number of employees currently. The implementation of E-ABK (Workload Analysis) for Employees at the Surabaya City Education Office has been going smoothly. Even though the infrastructure and human resources are available and sufficient, there are still some employees who still do not fully understand how to fill out E-ABK. To increase employee competency, regular outreach and training regarding the use of E-ABK is needed.